Development of Graphical User Interface for Checking Logic Circuit of AgSTEM Activity - Yukunthorn, Weera (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
In this paper, we developed SCILAB 6.0 to check working states of logic circuits via Boolean expression in AgSTEM activity. The graphical user interface (GUI) was investigated and developed as follows: 1) we defined and constructed mathematical objects and algorithms for computing and mapping between the systems of Boolean algebra and real numbers, 2) we designed and developed organizing objects and control objects to interpret states of working from Boolean expressions to the state table of the logic circuit and 3) we compared user time and accuracy of computing between computer and human. Consequently, the GUI which was investigated and developed can be compute between the system of Boolean algebra and real numbers. The states of working of logic circuits are presented as the truth table. So we obtained the GUI which computes both faster and more accurate than human.